2009
DOI: 10.1007/s10880-009-9156-9
|View full text |Cite
|
Sign up to set email alerts
|

Psychologists and Primary Care Physicians: A Training Model for Creating Collaborative Relationships

Abstract: For over a decade insurance reform, changes in health care delivery, reimbursement policies, and managed care have increased pressure on psychologists to diversify beyond traditional practices. Despite the negative impact of failing to make a transformation, most psychologists have not modified their practice and most training programs do not prepare psychologists to provide integrated care. The current paper describes the importance of primary care and psychology partnering to create integrated care models an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 35 publications
2
59
0
1
Order By: Relevance
“…3,11,22 Moreover, BHCs and PCCs are infrequently trained in collaboration or practicing in interprofessional settings. 6,17 Although increasing numbers of programs are emerging offering integrated care training for students, 6,11,[23][24][25][26] medical residents, 6,11,24,27,28 or postdoctoral trainees, 3 insufficient training capacity and practical experience opportunities continue to be major barriers to supplying the workforce needed for effective behavioral health and primary care integration. As practices and payers increasingly recognize the benefits of integrated care, the need and demand for competent clinicians to work in these integrated settings will grow.…”
Section: Discussionmentioning
confidence: 99%
“…3,11,22 Moreover, BHCs and PCCs are infrequently trained in collaboration or practicing in interprofessional settings. 6,17 Although increasing numbers of programs are emerging offering integrated care training for students, 6,11,[23][24][25][26] medical residents, 6,11,24,27,28 or postdoctoral trainees, 3 insufficient training capacity and practical experience opportunities continue to be major barriers to supplying the workforce needed for effective behavioral health and primary care integration. As practices and payers increasingly recognize the benefits of integrated care, the need and demand for competent clinicians to work in these integrated settings will grow.…”
Section: Discussionmentioning
confidence: 99%
“…Some high school 43 (18) 34 (21) 8 (14) 1 (6) High school graduate 107 (46) 70 (43) 27 (48) 10 (58) College graduate 40 (17) 26 (16) 10 (18) 4 (24) Professional/graduate 45 (19) 32 (20) 11 (20) 2 (12) Values provided as n (%). This study found a strong net relationship between insomnia severity and depression.…”
Section: Discussionmentioning
confidence: 99%
“…18 Preeminence of dysfunctional beliefs would warrant greater emphasis on the integration of cognitive-behavioral approaches in medical settings. 19 Knowing how relationships vary across sociodemographic subgroups can also inform management. Accordingly, this study was conducted to identify individual and net psychosocial correlates of insomnia severity and to determine whether these relationships vary with sociodemographic attributes.…”
mentioning
confidence: 99%
“…Recognized training programs are established at the psychology doctoral, internship, and fellowship levels in integrated primary care (Bluestein & Cubic, 2009;GarciaShelton & Vogel, 2002). A recent survey of Family Medicine residency programs in the United States indicated that 7% of residencies currently have (or in the recent past had) some type of embedded psychology training program (Vogel & Garcia-Shelton, 2009).…”
Section: Role In Formal Teaching and Supervisionmentioning
confidence: 99%
“…The training of psychologists is largely compartmentalized to the behavioral health professional culture, leaving them illprepared to function in primary care settings (Bluestein & Cubic, 2009;Kessler et al, 2009;O'Donohue, Cummings, & Cummings, 2009). In primary care cultures medical team members use brief patient encounters and prioritize medical and not psychological concerns.…”
Section: Foundational Characteristics Of the Primary Care Psychologismentioning
confidence: 99%